CREATING EXPERIMENTAL GARMENTS BASED ON CULTURAL HERITAGE ELEMENTS AND THEIR APPLICATION IN THE EDUCATIONAL PROCESS - Rajabova Nilufar Shuhratovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the creation of experimental garments based on cultural heritage elements and their integration into the educational process. It examines how traditional motifs, patterns, and colors can be adapted in modern garment design to enhance students’ creativity, technical skills, and cultural awareness. The study highlights pedagogical strategies for incorporating experimental design projects, handson workshops, and digital tools, making heritage-based design education interactive and effective for young learners.